Cultura digital jovem: as TIMS invadem as periferias, e agora? - Márcia Gonçalves Nogueira; Maria Auxiliadora Soares Padilha (Universidade Estadual de Campinas, 2014)
Objective of this work is to present a literature review on Young and the Digital Cultural transformations caused by the dissemination of Information Technology and Communication Mobile and wireless (TIMS) on the outskirts of the metropolitan area of Recife. To this end, we seek to identify how young periphery, high school students of a public school, they experience the Digital Culture in different social spaces; among them the school, scene of many tensions and generational conflicts and language as social and cultural use of these mobile devices. We highlight some theoretical approaches to the phenomenon of mobile communication and the concept of Digital Culture, adopted in this work. Proposing a reflection on the role of school in the current social context of constant cultural and linguistic transformations multimodality of the digital age. Finally, we present an exercise of looking on Youth Cultures, from different theoretical, to better understand the multiple transits covered by surveyed youth to express themselves and make sense of their audiovisual productions, mediated by TIMS. This theoretical argument was used in the dissertation in mathematics education and technology by one of the authors of this article. Therefore, we hope to contribute to further research on Digital Youth Culture in the context of the periphery.